Hubungan Motivasi Suami Dengan Sikap Istri Dalam Melakukan Pap Smear - Elfi Quyumi; Wahyuni H. S. Sully (Akademi Keperawatan Dharma Husada Kediri, 2012)
Its reducing motivates and ignorance hit pap smear of 200.000 total serviks's cancer patient at Indonesian just register 20% one has once do pap smear's checks. To the effect this research is subject to be know husband motivation relationship with wife attitude in do pap smear's check. Observational design that at utilizes deep observational be design correlation. Its free variable is motivate husband to pap smear's check and variable be tied-up is wife attitude in does pap smear. Wife husband population at RW. 02 RT. 03 Lirboyo's sub-districts as much 47 respondents. With technics simple random is sampling gotten by sample as much 38. Downloading by dealt out kuisioner, analysed to utilize coefficient statistic quiz kontingensi by programs SPSS 17 windowses. Result that gotten by researcher, 28,9% respondent lie on level motivates be and 52,6% respondent point out positive attitudes. Base statistic's quiz result is gotten Approx's point. Sig. as big as 0,000< 0,05 (alpha's point), keeratan is relationship includes in category be (pointed out by outgrows it contingency coefficient's point as big as 0,566), so H 0 refused and h 1 accepted. Its mean Available relationship motivates husband with wife attitude in does pap smear. Conclusion of this research that there is relationship among motivates husband with wife attitude in does pap smear. Expected by more health officer give information about pap smear so women has visceral more information and moved do pap smear.